Inoculation of phosphate solubilizing bacteria (PSB) on different level of soil pH towards paddy growth and phosphorus availability / Azlina Aziz Ja'afa - Aziz Ja'afa, Azlina (Faculty of Plantation and Agrotechnology, 2016)
Plants acquire phosphorus from soil solution as phosphate anion. It is the least mobile element in plant and soil contrary to other macronutrients. It precipitates in soil as orthophosphate or is absorbed by Fe and Al oxides through their exchange. Phosphorus solubilizing bacteria play role in phosphorus nutrition by enhancing its availability to plants through release from inorganic and organic soil P pools by solubilization and mineralization. Thus this study was carried out to identify the effectiveness of phosphate solubilizing bacteria (PSB) on different level of soil pH towards paddy growth and phosphorus availability. Four level of pH used in this study which were control (TO) soil pH is 6-6.5 without PSB application, followed by pH 4-4.5 (TI), pH 5-5.5 (T2) and pH 7-7.5 (T3). This study was conducted for 6 weeks and plant height of paddy was measured by weekly basis. The soil pH and the phosphorus availability also were analysed. From the result obtain, it showed that the pH value on soil was decrease when apply the PSB. Then, it increased the available P in the soil and decrease the total P. Based on the result, the best level of soil pH for apply the PSB is pH that range 5-5.5 (T2) after the 6-6.5 (TO).